A new "Mammy" in the age of digitalization; human insecurity versus utopian affective algorithms in Kazuo Ishiguro's Klara and The Sun - Mohamed Ahmed, Alshaymaa Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2024)
Science fiction has advanced beyond the depiction of artificial intelligence, which is capable of conscious thought to speculate on a future in which machines that feel and initiate feeling in return are created. This article discusses Kazuo Ishiguro's Klara and The Sun (2021) as a textual reference by considering circumstances in which emotional capacity no longer separates humans from machines. In most dystopian literature, political distinctions between humans and less-than-humans are typically used to describe the systems of governance, with the latter constituting the marginalised yet inexorable substratum that supports and normalises the dominant system. Drawing on Affect Literary Theory and its relevance to AI, I argue that, contrary to popular belief, Klara, the AI, can feel emotions such as sadness, grief, sympathy, love, faith, and hope. Nonetheless, rather than being pleased and comfortable, humans represented in Klara and the Sun contest AI's supremacy and use otherness as a defence mechanism to degrade AIs to feel superior and defend themselves from AI's likely rule of the planet. In Klara and the Sun, a disturbing historical parallel to the position of the AIs in the social hierarchy is that of slaves since, like slaves, their existence is reduced to their disposable utility. I can conclude that slavery expands to encompass the entire planet, with androids, genetically modified humans, and the earth itself functioning as sites of human capitalist exploitation. Using Affect Theory, I argue that Ishiguro attempts to elicit humans' sympathy and empathy with Klara, the AI, in order to advocate for a relationship in which humans have never been distinct from machines and conceptions of humanness could not be formulated without technologies.